2021
DOI: 10.7554/elife.69040
|View full text |Cite
|
Sign up to set email alerts
|

Common virulence gene expression in adult first-time infected malaria patients and severe cases

Abstract: Sequestration of Plasmodium falciparum-infected erythrocytes to host endothelium through the parasite-derived PfEMP1 adhesion proteins is central to the development of malaria pathogenesis. PfEMP1 proteins have diversified and expanded to encompass many sequence variants conferring each parasite a similar array of human endothelial receptor binding phenotypes. Here, we analyzed RNA-seq profiles of parasites isolated from 32 P. falciparum infected adult travelers returning to Germany. Patients were categorized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
138
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(139 citation statements)
references
References 97 publications
1
138
0
Order By: Relevance
“…Although var genes domains expression associated with CM has been extensively studied [ 13 , 17 , 18 ], the involvement of other parasite factors is not yet fully understood. Previous studies have shown that parasites display distinct gene expression profiles associated with severe malaria (SM) [ 5 , 6 ]. A more metabolically quiescent phenotype associated with SM was demonstrated [ 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although var genes domains expression associated with CM has been extensively studied [ 13 , 17 , 18 ], the involvement of other parasite factors is not yet fully understood. Previous studies have shown that parasites display distinct gene expression profiles associated with severe malaria (SM) [ 5 , 6 ]. A more metabolically quiescent phenotype associated with SM was demonstrated [ 5 ].…”
mentioning
confidence: 99%
“…A more metabolically quiescent phenotype associated with SM was demonstrated [ 5 ]. In addition, deregulated genes implicated in var genes expression or Pf EMP1 presentation to the iE membrane were identified [ 5 , 6 ]. In this study, we aimed to characterize P falciparum isolates’ gene expression in the context of pediatric malaria, by comparing the whole transcriptome of isolates from Beninese children enrolled in the NeuroCM study.…”
mentioning
confidence: 99%
“…PfEMP1 proteins have diverged in binding activity for CD36 and EPCR (Smith et al, 2013). Whereas previous work has linked EPCR or dual EPCR and ICAM-1 PfEMP1 variants to severe malaria (Lavstsen et al, 2012;Turner et al, 2013;Bernabeu et al, 2016;Kessler et al, 2017;Storm et al, 2019; Sahu Wichers et al, 2021), little is known about their endothelial binding specificity. Here, we provide evidence that the DC8 and Group A EPCR-binding PfEMP1 subsets have binding activity for brain, gut, and kidney endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, different subsets of PfEMP1 proteins encode binding activity for CD36 (Robinson et al, 2003;Hsieh et al, 2016), endothelial protein C receptor (EPCR) (Turner et al, 2013;Lau et al, 2015), and intercellular adhesion molecule 1 (ICAM-1) (Smith et al, 2000;Lennartz et al, 2019). Whereas the EPCR binders comprise only a small minority of the var gene repertoire (~10% of genes) (Rask et al, 2010), this subset is transcriptionally elevated in severe malaria infections and both the DC8 and Group A PfEMP1 variants are linked to severe malaria complications (Lavstsen et al, 2012;Turner et al, 2013;Bernabeu et al, 2016;Kessler et al, 2017;Lennartz et al, 2017;Mkumbaye et al, 2017;Sahu et al, 2021;Wichers et al, 2021). From in vitro studies, EPCR-binding variants adhere to human brain endothelial cells (Turner et al, 2013;Avril et al, 2016;Lennartz et al, 2017;Bernabeu et al, 2019;Storm et al, 2019) and to primary human heart and lung microvascular endothelial cells (Avril et al, 2013;Gillrie et al, 2015), suggesting they may have broad affinity for diverse microvascular beds.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear whether sST2 affects endothelial activation, endothelial activation affects sST2 levels, or if interactions occur both ways. Animal studies or studies of an in vitro blood-brain barrier could help to determine this [ 49 ]. Plasma sST2 levels may also, or instead, serve as a marker of brain injury, elevated as a specific response to cerebral ischemia and serving as a marker of neuroinflammation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%